Writing a Trans History of HIV/AIDS in Britain, 1985-1996 - Thompson, E (2023)
There is currently no trans history of the HIV/AIDS epidemic in Britain, despite modern transgender people being considered an ‘at-risk’ group. This thesis represents a first attempt to construct this history, focusing on archives over oral histories to contend head-on with how this history has been systemically un-seen. Analysing British gay and transfeminine organisations in the 1980s and 1990s – namely, comparing the relationship between The London TV/TS Group and the Lesbian and Gay Switchboard - this thesis argues that the pathological gaze of ‘transsexuality’ through the panopticon of NHS Gender Clinics prohibited subjects from conceiving trans people as susceptible to HIV/AIDS. In the style of Jules Gill-Peterson, this thesis introduces the framework of ‘transsexual eugenics’: the roots of transsexual medicine lay in eugenic science, and I argue that this relationship with eugenicism enforced its patients to rescind all attachments to life beyond heteronormativity, and AIDS was conceived as the antithesis of normativity through popular associations with homosexuality and sex work. After Chapter One establishes the theoretical basis in postcolonial and transgender theory, Chapter Two expands on ‘transsexual eugenics’ through arguing the largest trans organisations during the AIDS epidemic were too intertwined with Gender Clinics to realise their internalisation of eugenic rhetoric, thus rendering AIDS unthinkable alongside a diagnosis of transsexuality. Chapter Three concludes by analysing the reciprocal relationship between the London TV/TS Group and Switchboard to conclude that the transmission of eugenicist Gender Clinic rhetoric from the Group into Switchboard prevented Switchboard from delivering AIDS sexual health information to trans callers. This thesis hopes to inspire historical interest in the British trans history of HIV/AIDS, as well as further critiques of mid-twentieth century transsexual medicine.